How does USP transfer technology? - Dias, Alexandre Aparecido; Porto, Geciane Silva (Organizações & Sociedade, 2014)
The overall goal of this research is to verify how the University of São Paulo (USP) transfers its technologies to society. Thus, we performed a case study based on semi-structured interviews with the directors and innovation agents of USP Innovation Agency, which is the university Technology Transfer Office (TTO). It was found that the main mechanisms of technology transfer used by USP are: patent licensing, research and development (R&D) projects in partnership and foster and support the creation of spin-off companies. It was found that the USP Innovation Agency has a strong shortage of staff and that USP still lacks a stronger institutional policy that actually incorporates in its agenda the need to strengthen its role as a promoting innovation and technological development institution.